PENINGKATAN KONSENTRASI ANAK MELALUI METODE EKSPERIMEN MEMBUAT LAVA GUNUNG MERAPI - Dwi Nomi Pura; Aisyah Wulandari (Early Childhood Research and Practice, 2020)
This study aims to increase the concentration of children through the experimental method of making volcanic lava in HARAPAN BUNDA PAUD, Karang Tinggi Village, Karang Tinggi District, Central Bengkulu. This type of research is classroom action research (PTK). The subjects in this study were all children aged 5-6 years old, consisting of 24 children. Data collection techniques are done using observation, documentation. The results of the research after the implementation of playing activities to make Mount Merapi lava using experimental methods to increase children's concentration with the theme of the universe of the mountain sub-theme, the sub-themes of Mount Merapi in pre-cycle only reached 35.75% and in the first cycle, the first meeting reached 55.75%. the second meeting reached 64.25%. In the second cycle, the first meeting reached 83.75% and in the second syllable, the second meeting reached 86.75%, each indicator of creativity increased to 83.3%, which increased to 20 children from 24 children. This change is because in the first cycle the child does not get a direct approach, and the child is less interested in the game being carried out, while in the second cycle the child gets a direct approach and the child is interested in the game.